New filtration parameters from X-ray computed tomography for tight rock images - Krakowska-Madejska, Paulina (Geology, Geophysics and Environment, 2022)
New parameters are proposed to evaluate the filtration properties of rocks obtained on the basis of 3D interpretation of images from X-ray computed tomography. The analyzed parameters are: global average pore connectivity, average blind pore connectivity, blind pore coefficient per object and blind pore coefficient per branch. The 3D pore space from computed X-ray tomography must be subjected to a process of pore space transformation into a skeleton. Then, the presented parameters can be evaluated, taking into consideration the pore channels (branches), pore channel connection points (junctions) and blind pores (pore without connection to the other pore). The calculations were made for low porosity sandstones, mudstones, limestones, and dolomites which differ in terms of age and depth of present deposition. The global average pore connectivity reflects the degree of development of the pore space in which the formation fluid can flow. The higher the global average pore connectivity, the most complex the pore structure can be expected. The higher the parameter of the average blind pore connectivity, the worse are the filtration properties of the rock. The higher the concentration of blind pore coefficient per object or branch, the worse the filtration properties of the rock. Moreover, new parameters were compared with the Euler characteristic and coordination number, revealing a high consistency.